Consciousness is What Space Literally Creates - Hamidi, Nabil (My University, 2025)
Space originates or creates consciousness through three empirical principles: chronological priority, ontological independence, and necessary-condition analysis. First, science agrees that all consciousness originated in space: conscious organisms emerged within a spatial environment because spatial conditions already existed long before any neural or cognitive system evolved. Second, consciousness cannot exist without space, while space has clearly existed without consciousness. This second principle is universally recognized by scientists: space is a fundamental physical precondition, whereas consciousness is a later emergent property of biological evolution. Third, science agrees that no form of consciousness—human, animal, or any conceivable form—preceded the existence of space. Space existed 14 billion years ago, long before the appearance of neural systems. Therefore, because space predates all consciousness, because consciousness depends on spatial structure to exist, and because space did not depend on consciousness, the conclusion follows directly: space originates consciousness.